Structural analysis of endothelial projections from mesenteric arteries. (April 2017) - Maarouf, Nadia; Sancho, Maria; Fürstenhaupt, Tobias; Tran, Cam Ha; Welsh, Donald G.
Abstract: Objective: Endothelial and smooth muscle cells must communicate with one another to regulate arterial diameter. A key structure driving heterocellular communication is the endothelial projection, a thin extension that crosses the internal elastic lamina (IEL) making contact with smooth muscle. This study sought to define the precise structural composition of endothelial projections in the mesenteric circulation. Methods: Third‐ and fourth‐order mesenteric arteries from hamster were prepared for electron microscopy. Electron tomographic approaches were used to generate 3‐D compositional models of endothelial projections. Results: Endothelial projections were categorized based upon their proximity to smooth muscle or how many projections projected through an IEL hole. Irrespective of the initial categorization, endothelial projections were largely devoid of organelles except for sparse membranous structures observed near the tip, close to potential smooth muscle contact sites. Unexpectedly, it was the base of projections which were rich with organelles including the endoplasmic reticulum, ribosomes, vesicles, caveolae, and mitochondria. Conclusions: Electron tomographic techniques suggest that the base of endothelial projections is likely a dynamic site for signal regulation and contractile control. As projections are largely devoid of membranous organelles, their principal function appears to ensure electrical contact between the two cell layers.